Multimediale Unterstützung zum Lesen von Funktionsgraphen: Grundlagen, Anwendungen und empirische Untersuchung eines theoriegeleiteten Ansatzes zur Arbeit mit multiplen Repräsentationen (mathematica didactica, 2007)
The difficulties students have when working with graphs are well known by teachers and researchers. An idea to find a remedy is to illustrate essential mental operations externally. This is called supplantation. An approach applying supplantation in the field of graph interpretation is developed on base of theories of multimedia learning. In an empirical study practical and theoretical impacts are investigated. The results indicate that such a supplantation of mental operations on graphs can become a useful tool to support adequate understanding of graphs. Adjusting supplantation to individual abilities in more detail and applying supplantation principle in different mathematical contexts are interesting topics of further research. further research.